2016
DOI: 10.1111/bjh.14480
|View full text |Cite
|
Sign up to set email alerts
|

RB but not R‐HCVAD is a feasible induction regimen prior to auto‐HCT in frontline MCL: results of SWOG Study S1106

Abstract: Aggressive induction chemotherapy followed by autologous haematopoietic stem cell transplant (auto-HCT) is effective for younger patients with mantle cell lymphoma (MCL). However, the optimal induction regimen is widely debated. The Southwesterm Oncology Group S1106 trial was designed to assess rituximab plushyperCVAD/MTX/ARAC (hyperfractionated cyclophosphamide, vincristine, doxorubicin and dexamethasone, alternating with high dose cytarabine and methotrexate) (RH) versus rituximab plus bendamustine (RB) in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 32 publications
(47 reference statements)
3
27
4
Order By: Relevance
“…Two ongoing trials were identified that were not completed. Nine trials fulfilled inclusion criteria and were included in the systematic review and in the meta‐analysis (Eichhorst et al , ; Flinn et al , ; Herold et al , ; Knauf et al , , ; Niederle et al , ; Rummel et al , , ; Michallet et al , ; Chen et al , , NCT00877006) (Fig ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two ongoing trials were identified that were not completed. Nine trials fulfilled inclusion criteria and were included in the systematic review and in the meta‐analysis (Eichhorst et al , ; Flinn et al , ; Herold et al , ; Knauf et al , , ; Niederle et al , ; Rummel et al , , ; Michallet et al , ; Chen et al , , NCT00877006) (Fig ).…”
Section: Resultsmentioning
confidence: 99%
“…Median age of patients ranged between 58 and 74 years. Three trials included a population in which the median/mean age was below 60 years (Herold et al , ; Flinn et al , ; Chen et al , ). Three trials included patients with a median age above 65 years (Niederle et al , ; Rummel et al , ; Michallet et al , ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the response rates and PFS seen with the SCR regimen compare favourably with other less intensive induction regimens. For example, the CR rate with SCR was higher than that seen in prospective studies using BR (40%), R‐cladribine (52%), R‐CHOP (34–42%), and VR‐CAP (rituximab, cyclophosphamide, doxorubicin and prednisone plus bortezomib; 53%) (Kluin‐Nelemans et al , ; Robak et al , ; Chen et al , ; Le Gouill et al , ; Visco et al , ; Chang et al , ; Ruan et al , ; Tam et al , ). Furthermore, although MRD testing was only available for 14 responding patients, all were MRD‐negative after induction.…”
Section: Discussionmentioning
confidence: 95%
“…As highly efficient harvest of auto‐PBSC was observed during the first CHASER (data not shown), it is possible that a greater number of patients may proceed to ASCT if the harvest of auto‐PBSC is initiated during the first CHASER. Possibility that the harvest of auto‐PBSC in the early period of intensive induction chemotherapy may result in a highly efficient harvest was suggested in a recent phase II study . In that randomized phase II study by the Southwest Oncology Group that compared HyperCVAD/MA with rituximab and bendamustine with rituximab (S1106 study), stem cell collection was planned and carried out after the 3rd of 4 HyperCVAD/MA cycles.…”
Section: Discussionmentioning
confidence: 99%